2009
DOI: 10.1136/jnnp.2008.166603
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke dementia predicts poor survival in long-term follow-up: influence of prestroke cognitive decline and previous stroke

Abstract: Long-term follow-up of our large well-defined poststroke cohort indicated that in patients with acute stroke, dementia is a significant predictor of poor long-term survival and death from brain-associated causes. Prestroke cognitive decline seems to have an additional negative influence on survival, but previous stroke does not seem to affect survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 32 publications
1
44
3
Order By: Relevance
“…30 Tobacco was associated with post-stroke dementia. 10,19,24 Cohort study found that smoker associated with potential covariates and diagnosis of post-stroke dementia (OR 1.51, 95%CI; 0.89-2.58) 10 and alcohol consumption risk factors were more frequent in demented patients than no demented patients (OR 1.87, 95%CI; 1.02-3.44). 26 Third, stroke factors such as the previous stroke has been indicated as a risk factor for poststroke dementia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Tobacco was associated with post-stroke dementia. 10,19,24 Cohort study found that smoker associated with potential covariates and diagnosis of post-stroke dementia (OR 1.51, 95%CI; 0.89-2.58) 10 and alcohol consumption risk factors were more frequent in demented patients than no demented patients (OR 1.87, 95%CI; 1.02-3.44). 26 Third, stroke factors such as the previous stroke has been indicated as a risk factor for poststroke dementia.…”
Section: Resultsmentioning
confidence: 99%
“…30 Atrial fibrillation was associated with an increased prevalence of post-stroke dementia. 16,19,23 Multivariate analysis of predictors of post-stroke dementia demonstrated that atrial fibrillation was associated with dementia in stroke patients which is statistically significant (OR 1.29, 95%CI; 1.02 to 1.63). 30 Myocardial infarction was independent predictors of dementia in stroke patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Studies have also shown that poststroke dementia (PSD) increases the risk of recurrent vascular events. 4,5 However, no studies to date have examined the effect of CIND on poststroke recurrent vascular events or dependency. We hypothesize that CIND is associated with dependency, recurrent vascular events, and death following ischemic stroke.…”
mentioning
confidence: 99%